1998
DOI: 10.1111/j.1532-5415.1998.tb01008.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Zinc and Vitamin A Supplementation on Immune Response in an Older Population

Abstract: These data indicate that zinc supplementation improved cell-mediated immune response, whereas vitamin A had a deleterious effect in this older population. Further research is needed to clarify the clinical significance of these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(71 citation statements)
references
References 24 publications
1
66
0
Order By: Relevance
“…Male Balb/c 50 (C) 18 mg as zinc sulphate Increased mean survival (40) 50 (Z) C57Bl/6 mice 8 (C) 300 mg/kg of Zn for 25 d Improved thymic output (47) 8 (Z) Table 1) in the majority of the studies, Prasad et al (49) and Boukaiba et al (50) have found an increment of thymulin activity and improvement in response to skin-test antigens and taste acuity; Bogden et al (51) have reported some benefit exclusively for increased lymphocyte mitogen proliferative response; Cakman et al (52) have found enhanced IFN-g production by leucocytes; Fortes et al (53) report an increased number of cytotoxic T lymphocytes; Hodkinson et al (54) describe no effect on some markers of immunity (natural killer cells) or inflammation (C-reactive protein), but only increased the ratio of CD4/CD8 T lymphocytes at month 6; Kahmann et al (55) report reduced levels of activated T-cells and basal IL-6 release from peripheral blood mononuclear cells and improved T-cell response. Using higher doses of zinc, 40-220 mg/d with different lengths of treatment (Table 1), Duchateau et al (56) and Sandstead et al (57) have observed an improvement in response to skin-test antigens and taste acuity; an improved delayed type hypersensitivity reaction has been also found in a limited number of subjects by Cossack (58) and by Wagner et al (59) ; Prasad et al (60) found improved IL-2 mRNA.…”
Section: (Z)mentioning
confidence: 99%
“…Male Balb/c 50 (C) 18 mg as zinc sulphate Increased mean survival (40) 50 (Z) C57Bl/6 mice 8 (C) 300 mg/kg of Zn for 25 d Improved thymic output (47) 8 (Z) Table 1) in the majority of the studies, Prasad et al (49) and Boukaiba et al (50) have found an increment of thymulin activity and improvement in response to skin-test antigens and taste acuity; Bogden et al (51) have reported some benefit exclusively for increased lymphocyte mitogen proliferative response; Cakman et al (52) have found enhanced IFN-g production by leucocytes; Fortes et al (53) report an increased number of cytotoxic T lymphocytes; Hodkinson et al (54) describe no effect on some markers of immunity (natural killer cells) or inflammation (C-reactive protein), but only increased the ratio of CD4/CD8 T lymphocytes at month 6; Kahmann et al (55) report reduced levels of activated T-cells and basal IL-6 release from peripheral blood mononuclear cells and improved T-cell response. Using higher doses of zinc, 40-220 mg/d with different lengths of treatment (Table 1), Duchateau et al (56) and Sandstead et al (57) have observed an improvement in response to skin-test antigens and taste acuity; an improved delayed type hypersensitivity reaction has been also found in a limited number of subjects by Cossack (58) and by Wagner et al (59) ; Prasad et al (60) found improved IL-2 mRNA.…”
Section: (Z)mentioning
confidence: 99%
“…Below, we discuss the effects of different micronutrients including vitamin A, B6 and E, betacarotene and zinc all of which have been intensively studied (Belisle et al, 2008;Bogden et al, 1990;Corridan et al, 2001;De la Fuente et al, 2008;Duchateau et al, 1981;Fortes et al, 1998;Hodkinson et al, 2007).…”
Section: Micronutrientsmentioning
confidence: 99%
“…The effects of Zn on lymphocyte populations are more varied. One study reported that institutionalized healthy elderly (≥65y) subjects had increased numbers of activated (HLA-DR + ) CD4 + and cytotoxic lymphocytes after 3 months of zinc supplementation (25mg/d as zinc sulphate) (Fortes et al, 1998), while other studies 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 profiles (Kahmann et al, 2006). Zinc supplementation has also been tested for its potential enhancement of vaccination efficacy in the elderly although the results are inconclusive (Pae et al, 2012).…”
Section: Zincmentioning
confidence: 99%
“…The effect of zinc supplementation on lipid peroxides observed in our study was also accompanied by a signi®-cant increase in some T-cell subsets (Fortes et al, 1995), suggesting that the antioxidant effect of zinc may have affected directly T-cell proliferation. It has been suggested that the decreased lymphocyte proliferation observed in ageing may be due to the impaired activation of protein kinase C. Impaired activation of protein kinase C, could be attributed to changes in membrane¯uidity caused by increased lipid peroxidation (Eze, 1992).…”
Section: Discussionmentioning
confidence: 60%